2010
DOI: 10.1083/jcb.201002070
|View full text |Cite
|
Sign up to set email alerts
|

The MIS12 complex is a protein interaction hub for outer kinetochore assembly

Abstract: The NSL1 subunit structures interactions between the MIS12, NDC80, and KNL1 kinetochore complexes (see also a related paper by Maskell et al. in this issue).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
274
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(304 citation statements)
references
References 85 publications
(181 reference statements)
27
274
2
1
Order By: Relevance
“…1B), our lysine-specific cross-linker provided limited information about MIND-Spc25 interactions. Previous work identified the C-terminal region of Dsn1 as being important for interaction with Spc24 and Spc25 and suggested that it also shares the binding site with Cnn1 (20,22). Our cross-linking results support this interaction although we detected far fewer cross-links between Dsn1 and Spc24 than between Nsl1 or Mtw1 and Spc24.…”
Section: Resultssupporting
confidence: 45%
See 3 more Smart Citations
“…1B), our lysine-specific cross-linker provided limited information about MIND-Spc25 interactions. Previous work identified the C-terminal region of Dsn1 as being important for interaction with Spc24 and Spc25 and suggested that it also shares the binding site with Cnn1 (20,22). Our cross-linking results support this interaction although we detected far fewer cross-links between Dsn1 and Spc24 than between Nsl1 or Mtw1 and Spc24.…”
Section: Resultssupporting
confidence: 45%
“…S1). By pairing gel filtration and velocity sedimentation experiments, we found that MN exhibits a frictional ratio of 2.7 (19), consistent with its extremely elongated conformation as seen previously by negative-stain electron microscopy (17,18,20) (Fig. S1).…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…This gradient of concentration is illustrated in orange. When the nuclear envelope breaks down, spindle subunits are preferentially assembled where the concentration of RanGTP is high (Spc25), which face the inner kinetochore and interact with minichromosome instability 12 (Mis12) complex (Petrovic et al 2010;Maskell et al 2010). Recent studies showed that an oligomeric array of Ndc80 complexes move along the microtubules through biased diffusion (Powers et al 2009;Alushin et al 2010).…”
Section: Kinetochores: a Re-evaluationmentioning
confidence: 99%